On the Number of α-Labeled Graphs - Barrientos Christian; Minion Sarah (Discussiones Mathematicae Graph Theory, 2018)
When a graceful labeling of a bipartite graph places the smaller labels in one of the stable sets of the graph, it becomes an α-labeling. This is the most restrictive type of difference-vertex labeling and it is located at the very core of this research area. Here we use an extension of the adjacency matrix to count and classify α-labeled graphs according to their size, order, and boundary value.